Salivary cardiac-enriched FHL2-interacting protein is associated with higher diastolic-to-systolic-blood pressure ratio, sedentary time and center of pressure displacement in healthy 7-9 years old school-children - Vasileva, Fidanka; Font-Lladó, Raquel; Carreras-Badosa, Gemma; Roman-Viñas, Blanca; Cadellans-Arróniz, Aïda; López-Bermejo, Abel; Prats-Puig, Anna (Frontiers in Endocrinology, 2024)
Introduction Cardiac-enriched FHL2-interacting protein (CEFIP) is a recently identified protein, first found in the z-disc of striated muscles, and related to cardiovascular diseases. Our objectives are: 1) to quantify CEFIP in saliva in healthy 7-9 years old school-children; and 2) to assess the associations of salivary CEFIP concentration and blood pressure, physical (in)activity and physical fitness in these children. Methods A total of 72 children (7.6 ± 0.3 years) were included in the study, recruited in primary schools in Girona (Spain). A sandwich enzyme-linked immunosorbent assay was used (abx506878; Abbexa, United Kingdom) to quantify CEFIP in saliva. Anthropometric evaluation was performed [body mass, height and body mass index (BMI)]. Systolic and diastolic blood pressure were measured by means of an electronic oscillometer and the diastolic-to-systolic blood pressure ratio (D/S BP ratio) was calculated. Physical (in)activity [sedentary time and time spent in physical activity (PA)] were assessed by means of a triaxial Actigraph GT3X accelerometer (Actigraph, Pensacola, FL, USA) that children were instructed to wear for 24h during 7 conssecutive days. Finally, physical fitness (speed and agility, explosive power of legs, handgrip strength, flexibility and balance) were assessed through validated and standardized testing batteries. Results CEFIP was easily detected and measured in all saliva samples (mean concentration: 0.6 ± 0.2 pg/ml). Salivary CEFIP was positively associated with D/S BP ratio (r=0.305, p=0.010) and sedentary time (r=0.317, p=0.012), but negatively associated with PA in 7-9 years old school-children (r=-0.350, p=0.002). Furthermore, salivary CEFIP was related to lower level of balance i.e., higher center of pressure (CoP) displacement in these children (r=0.411, p<0.001). The associations of salivary CEFIP with D/S BP ratio (Beta=0.349, p=0.004), sedentary time (Beta=0.354, p=0.009) and CoP displacement (Beta=0.401, p=0.001), were maintained significant after adjustment for potential confounding variables such as age, gender and BMI in linear regression analyses. Conclusion CEFIP can be easily assessed in saliva as a promising biomarker associated with cardiovascular health in 7-9 years old school-children. Interestingly, higher salivary CEFIP concentration was related to higher D/S BP ratio, more sedentary time and higher CoP displacement i.e., lower level of balance in these children.